2019
DOI: 10.1108/f-07-2018-0085
|View full text |Cite
|
Sign up to set email alerts
|

Mega event management of formula one grand prix: an analysis of literature

Abstract: Purpose A comprehensive literature review of mega event management of dynamic sporting events is presented. The purpose of this paper is to learn from these mega events to prescribe mitigation strategies for improving cost performance while simultaneously minimising public disruption on formula one grand prix events. Knowledge accrued of challenges posed is theoretically applied to circuit construction and reestablishment processes involved in orchestrating a “street circuit” grand prix event. Design/methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 63 publications
(72 reference statements)
0
26
0
Order By: Relevance
“…), and the link strength is denoted by the proximity between nodes [48]. VOSviewer has been utilised to a plethora of topics ranging from contemporary trends in construction management technology [55] to mega-event orchestration such as the Formula One grand prix [56]. Researchers specifically note the capability of the technique to analyse large datasets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…), and the link strength is denoted by the proximity between nodes [48]. VOSviewer has been utilised to a plethora of topics ranging from contemporary trends in construction management technology [55] to mega-event orchestration such as the Formula One grand prix [56]. Researchers specifically note the capability of the technique to analyse large datasets.…”
Section: Methodsmentioning
confidence: 99%
“…Using VOSviewer, Akinlolu et al [55] were able to show, when analysing extant literature on construction health and safety, that Africa was substantially underrepresented in research and suggested this as an area for future research. Similarly, Chamberlain et al [56] were able to demonstrate that a lack of knowledge regarding mega-event managers has hindered researchers' ability to 'learn lessons' from previous mega-events. Analysing a database sample of publications using the approach delineated will give significant insight into the wider research domain [57].…”
Section: Methodsmentioning
confidence: 99%
“…Accompanying objectives are to (1) implement a science mapping technique (cf. Chamberlain et al, 2019) to outline research trends and network clustering as the basis for the development of a strategic roadmap. This roadmap identifies core emergent themes and trends in IoT research and importantly, implications for broader research; (2) identify and rank key drivers for successful adoption of the IoT and digitisation technologies in the construction sector, so that the finer nuances between them can be determined and thus generating greater insight; (3) identify weakness and deficiencies within the current research study and present remedial solutions and recommended priority themes for future studies.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the interpretivist philosophy was adopted (cf. Al-Saeed et al, 2019 ) to analyse the extant literature as part of a systematic literature synthesis, where each publication represented a unit of analysis ( Chamberlain et al, 2019 ). A limitation of the interpretivist philosophy is that researchers are prone to the risk of introducing confirmation bias – a phenomenon often associated with hermeneutic research with its emphasis on subjective interpretations ( Williams, 2000 ).…”
Section: Methodsmentioning
confidence: 99%